Punti di vista - Punti di contatto. Studi di letteratura e linguistica tedesca - BALLESTRACCI, Sabrina; GRAZZINI, SERENA (Biblioteca di Studi di Filologia Moderna, 2015)
The question on possible contact points between linguistics and literary studies has arisen several times in the international discussion on German studies. This volume takes part in this debate and, by enhancing the specific features of both fields of study, it aims at contributing to the search for new ways of comparison and scientific exchange. The eight essays collected in this miscellanea are characterized by the interpenetration of the literary and linguistic points of view, and develop paths of analysis in the following research fields: theory of literary comedy and of literary genres; linguistic studies of the literary text; language as an object of literary analysis; teaching of German as a second language (DaF).